Lightning strike and delamination performance of metal tufted carbon composites - Lombetti, D. M.; Skordos, Alexandros A. (Elsevier, 2018)
This paper reports the development of multifunctional composites based on the use of metallic tufting. Stainless steel and copper are used to modify the through thickness mechanical and electrical behaviour of epoxy/carbon composites. The mechanical performance is evaluated in mode I delamination and the electrical behaviour is assessed using conductivity measurements and lightning strike tests. Metal tufting improves the delamination resistance by approximately 200% and 100% and the through thickness conductivity by 250 and 20 times for copper and stainless steel reinforcement, respectively. Lightning strike damage is suppressed significantly, with internal damage decreasing by about 90% and 75% compared to unprotected laminates for copper and stainless steel tufting, respectively. In the case of copper tufting the protection is comparable to what is achieved by standard surface copper mesh. These findings show that copper tufted composites are an ideal solution in applications requiring advanced mechanical and electrical functionality.
Keywords: Hybrid composites; Delamination; Lightning Strike; Electrical properties; Tufting